Stem Cells and Stroke: Opportunities, Challenges, and Strategies - Burns, Terry C (2011)
INTRODUCTION: Stroke remains the leading cause of disability in the Western world. Despite decades of work, no clinically effective therapies exist to facilitate recovery from stroke. Stem cells may have the potential to minimize injury and promote recovery after stroke. AREAS COVERED: Transplanted stem cells have been shown in animal models to migrate to the injured region, secrete neurotrophic compounds, promote revascularization, enhance plasticity and regulate the inflammatory response, thereby minimizing injury. Endogenous neural stem cells also have a remarkable propensity to respond to injury. Under select conditions, subventricular zone progenitors may be mobilized to replace lost neurons. In response to focal infarcts, neuroblasts play important trophic roles to minimize neural injury. Importantly, these endogenous repair mechanisms may be experimentally augmented, leading to robust improvements in function. Ongoing clinical studies are now assessing the safety and feasibility of cell-based therapies for stroke. EXPERT OPINION: We outline the unique challenges and potential pitfalls in the clinical translation of stem cell research for stroke. We then detail what we believe to be the specific basic science and clinical strategies needed to overcome these challenges, fill remaining gaps in knowledge and facilitate development of clinically viable stem cell-based therapies for stroke.